The largest contributors, the least beneficiaries: the outcome of the 12th Malaysia General Election for the state of Sarawak / Shaharuddin Badaruddin and Suseela Devi Chandran - Badaruddin, Shaharuddin; Chandran, Suseela Devi (Universiti Teknologi MARA, Shah Alam, 2011)
12th Malaysian Election 2008 has given a new perspective in Malaysian politics. The achievement of the opposition party in denying two-third majority of the ruling party, the Barisan Nasional (National Front) in the Malaysian parliament has open up the new dimensions in the Malaysian political system. Among the outstanding states that helped the National Front (Barisan Nasional) to maintain the federal government were Sabah and Sarawak. Sabah and Sarawak can be considered as the biggest cash depositors in providing enough seats for the Barisan Nasional to control the federal government. Knowing well that Sabah and Sarawak states had ‘saved’ the National Front from possibly the first ever defeat since independence in 1957, the federal government is very much indebted to these two states. Using this opportunity, these two states have ‘demanded’ more attention from the federal government. The most important issues for these two states have always been the issue of development. However, the outcome is far from expectation. Winning 31 out of 32 seats does not give Sarawak the advantage in getting more post in the cabinet in compare to other states. This paper will provide a great deal of discussions on the issues that arises after the 12th General Election and the possibilities of political maneuvering in the near future.